Analysis of pathological manifestations in reinforced concrete structures: a review (Research, Society and Development, 2020)
The term pathology addressed in civil engineering comprises the study of the origin, treatment of building problems, representing aesthetic damage, reduction of building performance, and may impair the functionality of the building or its subsystems. Damage to reinforced concrete structures can be avoided even in the projects phase, several works present problems with pathological manifestations, problems that can be very costly their recovery. In this context, this article aims through a literature review study to analyze the main pathological incidences in reinforced concrete structures, in addition to proposing practical solutions to the problems, answers presented by the authors of the respective works of the case studies analyzed. This work was based on papers from the Google Acadêmico scientific literature database, totaling 15 studies, using the publications from January 2009 to January 2020, having the following keywords: Pathology of buildings, pathological analysis, civil construction, reinforced concrete and higher incidences. Through the literature addressed, it was possible to verify that of the pathologies analyzed, the most frequent is corrosion of the reinforcement, being present 100% of the studies analyzed and then stand out the incidences of pathologies of the type fissure and spots, with 73% and 60%, respectively. It was verified that the cracks represent 53% of the pathological manifestations found in the works; Eflorescencia (47%); Buckling (27%) and Carbonation (20%).